2023
DOI: 10.1101/2023.01.23.523609
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

TheMedicago truncatulanodule-specific cysteine-rich peptides, NCR343 and NCR-new35 are required for the maintenance of rhizobia in nitrogen-fixing nodules

Abstract: The Medicago truncatula-Sinorhizobium sp. symbiosis is one of the most effective nitrogen-fixing interaction. In the Inverted Repeat-Lacking Clade (IRLC) legumes, including M. truncatula, rhizobia undergo terminal differentiation resulting in elongated and endoreduplicated bacteroids specialised for nitrogen fixation. This irreversible transition of rhizobia is controlled by the host plant and mediated by nodule-specific cysteine-rich (NCR) peptides, of which about 700 are encoded by a large gene family in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(24 citation statements)
references
References 53 publications
3
21
0
Order By: Relevance
“…S2f-h, n-p). The morphology and bacterial occupancy of genome edited nodules were in agreement with the nodulation phenotype of Mtsym19 and Mtsym20 nodules defective in NCR-new35 13 . These results also revealed that NCR-new35 is crucial for the symbiotic interactions not only between M. truncatula 2HA and S. medicae WSM419 but between M. truncatula R108 and S. meliloti FSM-MA as well.…”
Section: Testing the Efficiency Of A Modified Vector For Crispr/cas9 ...supporting
confidence: 70%
See 4 more Smart Citations
“…S2f-h, n-p). The morphology and bacterial occupancy of genome edited nodules were in agreement with the nodulation phenotype of Mtsym19 and Mtsym20 nodules defective in NCR-new35 13 . These results also revealed that NCR-new35 is crucial for the symbiotic interactions not only between M. truncatula 2HA and S. medicae WSM419 but between M. truncatula R108 and S. meliloti FSM-MA as well.…”
Section: Testing the Efficiency Of A Modified Vector For Crispr/cas9 ...supporting
confidence: 70%
“…Therefore, the Arabidopsis U6-26 promoter was replaced with MtU6.6 in the pKSE401-RR resulting in the vector pKSE466-RR. We inserted the sgRNAs NCR169a and another one, targeting the NCR-new35, of which requirement for effective symbiosis has been recently demonstrated 13 , into pKSE466-RR, respectively. To validate the efficiency of the pKSE466-RR vector construct, the empty vector and pKSE466-RR-NCR169a were introduced into wild-type M. truncatula 2HA plants using A. rhizogenes-mediated hairy root transformation and plants were inoculated with S. medicae WSM419.…”
Section: Testing the Efficiency Of A Modified Vector For Crispr/cas9 ...mentioning
confidence: 99%
See 3 more Smart Citations